Africane-type sesquiterpenoids from the Argentine liverwort porella swartziana and their antibacterial activity - Bovi Mitre, Graciela (2004)
Seven africanes (1, 2a, b, 3-6), two of them new (1, 2a) three secoafricanes (7, 9), one of them new (7), and two norsecoafricanes (10, 11a), one of them new (10), all of them swartzianin-type, have been isolated from an Argentine collection of the endemic liverwort Porella swartziana. The structures of the new compounds were established by extensive 1D and 2D NMR spectroscopic data. Absolute configurations of compounds 2a, 2b and 10 were derived on the basis of CD spectra. The compounds were tested for activity against a variety of microbes, but none were found to exhibit significant antibacterial activity.